Analisis Faktor Penyebab Ketidakakuratan Kode Diagnosis Utama Injury dan External causes pada Rekam Medis Rawat Inap di RSD dr. Soebandi Jember - Novita Nuraini; Dyah Palupi Budiningsih; Maya Weka Santi; Dony Setiawan; Hendyca Putra (Indonesian Journal Publisher, 2024)
The inaccurate coding of primary injury and external causes diagnoses is a classification issue in the ICD-10, posing risks of financial loss for hospitals and compromising the validity of statistical data. Between 2020 and 2022, the coding accuracy for inpatient injury diagnoses at RSD Dr. Soebandi Jember was 70%, while external100% inaccuracy because were not coded at all. This research aimed to analyze the factors causing inaccuracies in coding these diagnoses based on the Robbin performance theory and propose improvement strategies through brainstorming. In this qualitative study, data was collected through in-depth interviews, observations, and document analysis. Findings revealed ablity factor cause by the lack of Emergency Room physicians knowledge’s in completing injury case histories and discrepancies in medical terminology selection by attending physicians. Motivation factors were identified suboptimal reward and punishment systems, and the absence of feedback in evaluating medical record quality. The opportunity factor encompassed unclear task boundaries between coders and internal verifiers, and the coding process deviated from standard operating procedures (SOP). Suggestion to address these issues, re-socialization of SOPs related to coding procedures, advocating for appropriate reward and punishment, and organizing internal training on injury and external causes diagnosis coding.